Smart Repetition dan Brain Wave Technology dalam Pembuatan Audio Book Kosa Kata Bahasa Inggris - Raden Arfan Rifqiawan (LP2M of Institute for Research and Community Services - UIN Walisongo, 2016)
Research work, devotion lecturers are embodied with mentoring activity, making audiobook and a mastery vocabulary English often used with Smart Repetition and Brain Wave technology. Making audiobook with Smart Repetition and Brain wave technology done together the participants capital. Making audiobook it is not easy that calls for exercise and patience participants capital .But through frequent exercise , finally they can make audiobook according to what they want. Assistance mastery vocabulary English often used with Smart Repetition and Brain Wave technology do with some stage.An early stage done by building community using application Telegram.The next stage is for the delivery of material, training, and the interaction continuously between researchers and participants cooperate either directly or online until the participants cooperate graduated from college.